Factors Affecting the Increasing Incidence of Early Marriage in Bola District, Wajo Regency - Yammar Yammar; Masrah Hasan; Fatmawati Fatmawati (NurseLine Journal, 2022)
Teenagers under the age of 19 who get married without any readiness to marry are considered as early marriages. Early marriage in general has become a serious problem throughout the world, including in Indonesia, especially in Bola District, Wajo Regency. The incidence of early marriage in Bola District, Wajo Regency, increased from 2020 to 2021, though the incidence of early marriage began to decrease in 2022. The purpose of this study is to determine the factors that affect the increasing incidence of early marriage in Bola District, Wajo Regency. The type of research used is observational with a cross sectional research design. The population of this study were adolescents who married at an early age that were registered at the Office of Religious Affairs ( KUA) Bola District, Wajo Regency. The subject of this study was taken by looking at the list of persons in the Bola District KUA from 2020-2022 who were married under the age of 19 years. The total number of research subjects from 2020-2022 is 115. The type of statistical test used to test each of the factors that affect the increasing incidence of early marriage in Bola District, Wajo Regency, was Chis-Quare Test. Results: The level of knowledge of the early marriage subjects in 2020-2022 concerning the impact of early marriage turned out to be low. In addition, the role of family members regarding early marriage was more negative, while the economic status of the family was more of the lower class. The three factors significantly increase the incidence of early marriage from 2020 to 2021, namely from 40 to 50 early marriages. However, in 2022 (January-August) the incidence of early marriage began to decrease. There are three factors that significantly affect the increasing incidence of early marriage in Bola District, Wajo Regency, namely the level of knowledge of the subjects, family economic status and the role of family members.